A comparative study of intrathecal levobupivacaine-clonidine and bupivacaine in the quality of anesthesia for patients undergoing hernioplasty - Sayantan Dutta; Sushmita Das; Debasish Saha; Nayak, Jisnu (Asian Journal of Medical Sciences, 2023)
Background: Bupivacaine is most commonly used amino-amide drug for subarachnoid block in hernioplasty. Levobupivacaine has similar pharmacological activity to that of bupivacaine with minimal cardiotoxicity. Clonidine, an α2 adrenergic agonist, potentiates the action of local anesthetics when used intrathecally and enhances post-operative analgesia. Aims and Objectives: This prospective, comparative, observational study was aimed to compare the effects of 0.5% levobupivacaine with clonidine and 0.5% hyperbaric bupivacaine in patients undergoing hernioplasty for the quality of surgical anesthesia and hemodynamic changes with any significant intraoperative complications. Materials and Methods: After receiving approval from the institutional ethics committee and written informed consent, 80 male patients aged between 18 and 60 years, BMI <30 kg/m2, height>150 cm, and American society of anesthesiologists physical status1 and 2 posted for elective hernioplasty were enrolled into two equal groups of 40 patients, group LC and group B. Patients in group LC received 15 mg 0.5% isobaric levobupivacaine with 30 μg clonidine and patients in group B received 15 mg hyperbaric bupivacaine intrathecally. SPSS version 20 was used for analysis, and P<0.05 was considered statistically significant. Results: In group LC, onsets of both sensory and motor blocks were delayed, whereas durations of motor and sensory block with analgesia were longer. Tachycardia, hypotension, nausea, vomiting, and shivering were observed greater in numbers in group B, whereas incidence of bradycardia was more in group LC. Conclusion: Prolonged duration of sensory and motor block, prolonged analgesic effect, and hemodynamic stability without any significant adverse effects may make this combination a better alternative to hyperbaric bupivacaine for hernioplasty.